Heterojunction of SnO2 nanosheet/arrayed ZnO nanorods for humidity sensing - M.H. Mamat; A.S. Ismail; Norfarariyanti Parimon; N. Vasimalai; M.H. Abdullah; M.F. Malek; M.K. Yaakob; M.K. Ahmad; N. Nafarizal; A.B. Suriani; A. Mohamad; M.D. Birowosuto; et al. (Elsevier, 2022)
For the first time, a rutile phased tin oxide (SnO2) nanosheet was assembled onto a zinc oxide (ZnO) nanorod array to form SnO2 nanosheet/ZnO nanorod array heterostructure films (TSZR) using a two-step solution immersion method. This study offers a facile and effective path to grow a SnO2 nanosheet assembled layer on ZnO nanorod arrays with a varied density using a tin (II) chloride dihydrate precursor to achieve an optimum humidity sensing response through the SnO2 growth time from 1 to 5 h. The structural characteristics, electrical properties, and humidity sensing response of the heterostructure films were investigated using various characterization techniques, such as field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, high-resolution transmission electron microscopy, X-ray diffraction, atomic force microscopy, Raman spectroscopy, a two-probe current-voltage measurement, and a humidity sensing response measurement system. The synthesized ZnO nanorods have an average diameter of 90 nm, while the grown SnO2 nanosheets have an average width of 20 nm. The humidity response performance of the films demonstrates a remarkable dependence on the SnO2 nanosheet assembled layer on the ZnO nanorod array film with the best humidity sensitivity of 754.4 at room temperature obtained for the 2 h-grown SnO2 nanosheet-based 2TSZR heterostructure sample. The 2TSZR sample also exhibited good stability over a four-cycle measurement and magnified current value of the humidity sensing response at a high operating temperature up to 60 °C. These investigations reveal that the TSZR heterostructure films are promising for humidity sensing devices with high sensitivity.